SOCIOBIOLOGY OF AN ALL MALE BAND IN HANUMAN LANGURS, PRESBYTIS ENTELLUS AROUND JODHPUR - RAJPUROHIT, LAL SINGH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
The genetically isolated population of about 1300 langurs (Presbytis entellus) around Jodhpur organised in unimale bisexual multimale bisexual and all male groups. The male band comprised of only males of different age classes except infants. The male infants are weaned earlier than female infants at about 13 months age (range 12 to months). These weaned male infants are expelled from bisexual groups and become members of all male bands. This sociobiological study (1983-88) suggest a definite social association among male langurs enabling them to live in harmony.